The Mitogen-Activated Protein Kinase Kinase VdPbs2 of Verticillium dahliae Regulates Microsclerotia Formation, Stress Response, and Plant Infection - Tian, Longyan; Wang, Yonglin; Yu, Jun; Xiong, Dianguang; Zhao, Hengjun; Tian, Chengming (Frontiers in Microbiology, 2016)
Verticillium dahliae, a ubiquitous phytopathogenic fungus, forms resting structures, known as microsclerotia that play crucial roles in Verticillium wilt diseases. VdHog1, a mitogen-activated protein kinase (MAPK), controls microsclerotia formation, virulence, and stress response in V. dahliae. In this study, we present detailed evidence that the conserved upstream component of VdHog1, VdPbs2, is a key regulator of microsclerotia formation, oxidative stress and fungicide response and plant virulence in V. dahliae. We identified VdPbs2, homologous to the yeast MAPK kinase Pbs2. Similar to the VdHog1 deletion mutant, VdPbs2 deletion strains exhibited delayed melanin synthesis and reduced formation of microsclerotia. When exposed to stresses, VdPbs2 mutants were more sensitive than the wild type to osmotic agents and peroxide, but more resistant to inhibitors of cell wall synthesis and some fungicides. Finally, VdPbs2 deletion mutants exhibited reduced virulence on smoke tree and tobacco seedlings. When taken together, we implicate that VdPbs2 and VdHog1 function in a cascade that regulates microsclerotia formation and virulence, but not all VdHog1 dependent functions are VdPbs2 regulated. This study thus provides novel insights into the signal transduction mechanisms that regulate microsclerotia formation and pathogenesis in this fungus.